Psychological distress among re-education through labour camp detainees in Guangxi Autonomous Region, China - Lorraine Yap; Su Shu; Lei Zhang; Wei Liu; Yi Chen; Zunyou Wu; Jianghong Li; Handan Wand; Basil Donovan; Tony Butler (Journal of Mental Health, 2017)
[Background:] There is currently no information about the prevalence of, and factors contributing to psychological distress experienced by re-education through labour camp detainees in China. [Methods:] A cross-sectional face-to-face survey was conducted in three labour camps in Guangxi, China. The questionnaire covered socio-demographic characteristics; sexually transmissible infections (STIs); drug use; psychological distress (K-10); and health service usage and access inside the labour camps. K-10 scores were categorised as ≤30 (low to moderate distress) and0.167em >30 or more (highly distressed). Univariate and multivariate logistic regression models identified factors independently associated with high K-10 scores for men and women separately. [Results:] In total, 755 detainees, 576 (76%) men and 179 (24%) women, participated in the health survey. The study found 11.6% men versus 11.2% women detainees experienced high psychological distress, but no significant gender differences were observed (p>0.167em0.05). Multivariate logistic regression showed that multiple physical health problems were significantly associated with high psychological distress among men. [Conclusion:] Drug treatment and forensic mental health services need to be established in detention centres in China to treat more than 10% of detainees with drug use and mental health disorders.
Keywords: 330; prisoners; China; psychological distress; K-10; labour camps